From water to land: how an invasive clam may function as a resource pulse to terrestrial invertebrates - Novais, Adriana (2015)
Resource pulses are episodes of low frequency, large magnitude and short duration that result in increased resource availability in space and time, with consequences for food web dynamics. Studies assessing the importance of resource pulses by invasive alien species in the interface between terrestrial and aquatic ecosystems are rare, especially those in the direction from water to land. This study assessed the importance of massive die-offs of the Asian clam Corbicula fluminea (Müller, 1774) as a resource pulse to the terrestrial invertebrate community after an extreme climatic event using a manipulative experiment. We used 5 levels of C. fluminea density (0, 100, 500, 1000 and 2000ind·m(-2)), with terrestrial invertebrates being censused 7, 30 and 90days after C. fluminea addition. We also assessed the possible effect of plots position, where plots that delimited the experiment were assigned as edge plots and the remaining as core plots. Clear differences were detected in abundance, biomass, richness and diversity of terrestrial invertebrates depending on the C. fluminea density, time and position. Interestingly, the highest abundance of adult Diptera was observed 7days after C. fluminea addition, whereas that of the other terrestrial invertebrates was on day 30, both with C. fluminea densities higher than 500ind·m(-2) located on the edge of the experimental design. This study highlights the importance of major resource pulses after massive die-offs of invasive bivalves, contributing with remarkable amounts of carrion for adjacent terrestrial systems. Part of this carrion can be consumed directly by a great number of invertebrate species while the remainder can enter the detrital food web. Given the high density and biomass attained by several invasive bivalves worldwide and the predicted increase in the number, intensity and magnitude of extreme climatic events, the ecological importance of this phenomenon should be further investigated.